EM-AUC: A Novel Algorithm for Evaluating Anomaly Based Network Intrusion Detection Systems - Kevin Z. Bai; John M. Fossaceca (Sensors)
Effective network intrusion detection using anomaly scores from unsupervised machine learning models depends on the performance of the models. Although unsupervised models do not require labels during the training and testing phases, the assessment of their performance metrics during the evaluation phase still requires comparing anomaly scores against labels. In real-world scenarios, the absence of labels in massive network datasets makes it infeasible to calculate performance metrics. Therefore, it is valuable to develop an algorithm that calculates robust performance metrics without using labels. In this paper, we propose a novel algorithm, Expectation Maximization-Area Under the Curve (EM-AUC), to derive the Area Under the ROC Curve (AUC-ROC) and the Area Under the Precision-Recall Curve (AUC-PR) by treating the unavailable labels as missing data and replacing them through their posterior probabilities. This algorithm was applied to two network intrusion datasets, yielding robust results. To the best of our knowledge, this is the first time AUC-ROC and AUC-PR, derived without labels, have been used to evaluate network intrusion detection systems. The EM-AUC algorithm enables model training, testing, and performance evaluation to proceed without comprehensive labels, offering a cost-effective and scalable solution for selecting the most effective models for network intrusion detection.